DIAGNOSING ODONTOGENIC SINUSITIS OF ENDODONTIC ORIGIN - Ruziyeva Sitora Saparovna (Web of Journals Publishing, 2023)
Nowadays, ensuring the complete recovery of patients diagnosed with odontogenic sinusitis is one of the urgent problems. That is, in this disease, a dentist and an otorhinolaryngologist must carry out joint treatment. Dentists are required to carry out quality treatment. In this case, it is also important to use quality fillers.
Keywords: apical and marginal periodontitis, maxillary sinusitis, odontogenic sinusitis, periapical lesion, depulpation, adseal